INTERNATIONAL AND NATIONAL RESEARCH METHODS ON REGIONAL TOURISM - Anvarova Muhsinakhon Otabek kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  scientific  article  examines  International  and  National Research  Methods  on  Regional  Tourism,  focusing  on  their  comparative  features, methodological  frameworks,  and  practical  implications  for  sustainable  tourism development.  The  study  employs  a  mixed-methods  approach  that  integrates  both quantitative and qualitative research designs to analyze the effectiveness of different methodological  models  in  regional  tourism  studies.  Through  literature  review, statistical evaluation, and case study analysis, the research identifies the strengths and limitations  of  international  and  national  approaches.  The  results  indicate  that international research methods provide valuable global comparability, while national methods offer deeper contextual understanding. The article concludes that a hybrid model — combining international analytical rigor with national contextual sensitivity —  ensures  more  accurate,  inclusive,  and  sustainable  outcomes  in  regional  tourism development. Recommendations are provided for improving data systems, promoting cross-border  academic  collaboration,  and  aligning  research  with  sustainable development goals (SDGs).